O direito linguístico no Brasil do século XXI: a materialidade das políticas linguísticas a partir do discurso internacional - Marques, Ricardo Felipe Facioni (2015)
This study has the objective of analyzing, based on the theory of Discourse Analysis, the functioning of the discourse materialized on the Universal Declaration of Linguistic Rights (1996), with special focus on the linguistic right and the label of official language. The second step is to verify the resignification of these terms and processes on the Brazilian Law, indeed the Inventário Nacional da Diversidade Linguística (2010) and the Política Estadual de Apoio as Comunidades Indígenas do Paraná (2004). The objects have been chosen because of their recognized importance for the linguistic policies in Brazil. According to this, this research consists in the analysis of these laws from the materialist discourse perspective, analyzing the ideological and symbolical processes that compose them. The study considers, in the same way, the relations of power and the historic conditions that are mise en scène. This process helps to identify the ruptures of signification and the Vergessen in each document that shows a continuity of linguistic policies practices since the colonial period and also the inscription of an economic model throw the diversity discourse. The research is based mainly on studies of Pêcheux (1980; 1993[1969]; 2008[1983]; 2009[1988]; 2010[1975]), Orlandi (2001; 2007; 2008; 2012), Zoppi Fontana( 2009) and Mariani (1993; 2003; 2004; 2008), in the theoretical part of Discourse Analysis, as well as in authors from Linguistic Policies as Altenhofen (1996; 2013; 2014) and Oliveira (2003; 2013). With this organization, we seek to articulate the political and ideological forms that appear in laws, desmystiying the transparency of language on the legal documents about linguistic rights